1
$\begingroup$

I recently got this question in my yearly mathematics exam and was one of the questions I calculated wrong.

What I did was :- $$\lim_{x\to 0}{\frac{\tan{x}-\sin{x}}{x^3}}$$ $$=\lim_{x\to 0}{\frac{\tan{x}}{x^3}}-{\frac{\sin{x}}{x^3}}$$ $$=\lim_{x\to 0}{\frac{\to 0}{x^2}}-{\frac{\to 0}{x^2}}$$ $$=\lim_{x\to 0}{(\to 0)({\frac{1}{x^2}}-{\frac{1}{x^2}})}=0$$ which is wrong. The correct answer is $\frac{1}{2}$ as given by wolfram alpha.

So my question is :-

1) What's the error in my answer?

2) How is the correct answer to be calculated?

Thanks for help :)

$\endgroup$
3
  • $\begingroup$ I would just start with L'Hopital's rule from the very beginning. $\endgroup$ Mar 9 '18 at 18:06
  • $\begingroup$ You have an indeterminate form, both the numerator and the denominator are going to zero, so you can't conclude much without more work. $\endgroup$ Mar 9 '18 at 18:09
  • $\begingroup$ What I wanted to say is that just like $lim_{\x to 0}{x-x}=0 why can't we say =\lim_{x\to 0}{({\frac{1}{x^2}}-{\frac{1}{x^2}})}=0? $\endgroup$ Mar 9 '18 at 18:16
3
$\begingroup$

The following step in you calculation was wrong:

$$=\lim_{x\to 0}{\frac{\tan{x}}{x^3}}-{\frac{\sin{x}}{x^3}}$$ $$=\lim_{x\to 0}{\frac{\to 0}{x^2}}-{\frac{\to 0}{x^2}}$$

You didn't write it down, but in order to do this you need to do an additional step, that is:

$$\lim_{x\to 0}{\frac{\tan{x}}{x^3}}-{\frac{\sin{x}}{x^3}}$$ $$=\lim_{x\to 0}{\frac{\tan{x}}{x^3}}-\lim_{x\to 0}{\frac{\sin{x}}{x^3}}.$$

But the above is not true. Separating sums in limits is only valid, if the limits of both summands exist and are finite, but in this case they don't.


A valid calculation of the limit would for example be:

\begin{align} &\lim_{x\to 0}{\frac{\tan{x}-\sin x}{x^3}} \\ =& \lim_{x\to 0} \frac {\tan x}x \frac{1-\cos x}{x^2} \\ =& \lim_{x\to 0} \frac {\tan x}x \lim_{x\to 0}\frac{1-\cos x}{x^2} \\=&1\cdot \frac 1 2 =\frac 1 2. \end{align} Here we can calculate each limit separately and multiply them afterwards, as both exist.
(In the first step I just took the $\tan x$ factor outside).

$\endgroup$
0
$\begingroup$

Hint: Use the Taylor development: $sin(x)=x-x^3/6+O(x^3)$, $tan(x)=x+x^3/3+O(x^3)$.

$\endgroup$
1
  • 3
    $\begingroup$ the order of the truncation error is surely $O(x^5)$, isn't it? $\endgroup$
    – nluigi
    Mar 9 '18 at 18:47
0
$\begingroup$

we have $$\frac{-\sin(x){\cos(x)}+\sin(x)}{\cos(x)x^3}=\frac{\sin(x)(1-\cos^2(x))}{x^3\cos(x)(1+\cos(x))}=\frac{\sin^3(x)}{x^3}\frac{1}{\cos(x)(1+\cos(x))}$$

$\endgroup$
0

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.